2019
DOI: 10.1029/2019jb018190
|View full text |Cite
|
Sign up to set email alerts
|

Three‐Dimensional Modeling of Spontaneous and Triggered Slow‐Slip Events at the Hikurangi Subduction Zone, New Zealand

Abstract: At the southern Hikurangi margin, New Zealand, long‐term (duration of >1 year), deep (>25 km) slow‐slip events (SSEs) occur at intervals of approximately 5 years. In contrast, along the northern and central Hikurangi margin, short‐term and shallow (<10 km) SSEs (2‐ to 3‐week duration) occur at 1‐ to 2‐year intervals. However, it is not clear what controls these differences in SSE behavior. In this study, we simulate SSEs along the entire Hikurangi subduction zone using a 3‐D model of the plate boundary incorpo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
22
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
3

Relationship

4
5

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 89 publications
2
22
0
Order By: Relevance
“…Numerical models using the empirical rate-and-state friction law can simulate the slip and stress history on the fault during earthquake cycles spanning a continuum spectrum of fast and slow slip [e.g. 25,26,27,28,29,31,32,38,49]. For example, Kaneko et al [30] showed that interseismic fault coupling pattern is highly related to the heterogeneous frictional properties on the fault, which suggests that geodetic inversions of fault locking can be used to inform the rate-state frictional parameter distributions in such earthquake sequence models and hence to quantitatively assess earthquake rupture scenarios.…”
Section: Introductionmentioning
confidence: 99%
“…Numerical models using the empirical rate-and-state friction law can simulate the slip and stress history on the fault during earthquake cycles spanning a continuum spectrum of fast and slow slip [e.g. 25,26,27,28,29,31,32,38,49]. For example, Kaneko et al [30] showed that interseismic fault coupling pattern is highly related to the heterogeneous frictional properties on the fault, which suggests that geodetic inversions of fault locking can be used to inform the rate-state frictional parameter distributions in such earthquake sequence models and hence to quantitatively assess earthquake rupture scenarios.…”
Section: Introductionmentioning
confidence: 99%
“…Numerical models using the empirical rate-and-state friction law can simulate the slip and stress history on the fault during earthquake cycles spanning a continuum spectrum of fast and slow slip (e.g. [18][19][20][21][22][23][24][25][26]). For example, Kaneko et al [27] showed that interseismic fault coupling pattern is highly related to the heterogeneous frictional properties on the fault, which suggests that geodetic inversions of fault locking can be used to inform the rate-state frictional parameter distributions in such earthquake sequence models and hence to quantitatively assess earthquake rupture scenarios.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, the Kapiti SSEs sequence in New Zealand is well-recorded with a long history as well. The recurrence intervals before the 2016 M w 7.8 Kaikōura earthquake are approximately 5.0 years, have been shortened to 0.5 years after the Kaikōura earthquake (Shibazaki et al 2019;Wallace et al 2018). This observation has a chance to support the Boso SSEs study if the future Kapiti SSEs keep the increasing recurrence intervals with time.…”
Section: Introductionmentioning
confidence: 73%